2017
DOI: 10.1080/02646838.2017.1297890
|View full text |Cite
|
Sign up to set email alerts
|

Nordic fathers’ willingness to participate during pregnancy

Abstract: Fathers wanted to participate and be responsible from the beginning of pregnancy. Fathers' participation in pregnancy involves a wide range of activities and strategies both within the domestic and the professional care-giving sphere. Health care professional's approaches to the father-to-be can enhance or reduce experiences of inclusion in antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(74 citation statements)
references
References 27 publications
2
41
0
23
Order By: Relevance
“…The first theme cluster, "preparing to become a father," contains experiences related to participants' mindset and behavior, which changed due to the presence of a baby. According to a previous study, expectant fathers were able to acknowledge the baby's presence by attending prenatal ultrasound appointments, speculating about the baby's personality, and naming the baby [19], similar to the results of this study. Providing expectant fathers an opportunity to recognize the fetus through ultrasound images is very important as it becomes the basis for attachment to the child [6,7].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The first theme cluster, "preparing to become a father," contains experiences related to participants' mindset and behavior, which changed due to the presence of a baby. According to a previous study, expectant fathers were able to acknowledge the baby's presence by attending prenatal ultrasound appointments, speculating about the baby's personality, and naming the baby [19], similar to the results of this study. Providing expectant fathers an opportunity to recognize the fetus through ultrasound images is very important as it becomes the basis for attachment to the child [6,7].…”
Section: Discussionsupporting
confidence: 86%
“…Providing expectant fathers an opportunity to recognize the fetus through ultrasound images is very important as it becomes the basis for attachment to the child [6,7]. Expectant fathers performed practical activities such as letting the fetus hear their voices, touching their wife's belly, and sensing fetal movement as the pregnancy progressed [19]. Participants in this study tended to value not only interactions with the baby, but also their mindset towards the baby in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…The attitude that permeates prenatal services is, from the perspective of future fathers, a not very inclusive practice regarding the father figure. They feel excluded by health professionals, who focus their care on the woman and the fe-tus, not recognizing them as equal partners in the transition, as shown in other studies [44][45][46][47] .…”
Section: Discussionmentioning
confidence: 91%
“…Further, some of the known individual barriers including men's education level, income, and limited awareness of men's role in reproductive health, hinder this partnership [1,[5][6][7][8]. A study to illuminate expectant first-time fathers' experiences of participation during pregnancy in three Nordic countries (Denmark, Finland and Sweden) showed that fathers wanted to participate and be responsible from the beginning of pregnancy [12]. The men's need to education to enhance participation in prenatal, delivery, and postnatal care as well as its positive effects on maternal and neonatal health has been shown in numerous studies in different countries [1,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%